Degradation behaviour and damage mechanisms of carbon fibre reinforced polymer composite laminates subjected to laser irradiation - Patrick K. Kamlade; Jojibabu Panta; Max Mammone; Richard (Chunhui) Yang; Richard P. Mildren; John Wang; Matthew Ibrahim; Rodney Thomson; Y.X. Zhang (Composites Part C: Open Access)
This study presents a comprehensive and insightful investigation into the thermal degradation and damage mechanisms of carbon fibre reinforced polymer (CFRP) composite laminates exposed to continuous wave laser irradiation with a Gaussian beam profile. The effects of laser power, beam diameter, and exposure time were explored to reflect practical scenarios such as material processing, maintenance, and damage assessment. Thermogravimetric analysis (TGA) was first carried out in both nitrogen and air environments to understand the thermal stability and degradation behaviour of the CFRP material. Initial laser tests were conducted at 30 W and 40 W using a beam diameter of 3.46 mm to assess early-stage damage. These results informed a more intensive study using a higher laser power of 98 W with beam diameters of 3.18 mm and 5.70 mm, where specimens were irradiated until complete perforation. Thermal imaging was used to monitor surface temperature evolution on both front and back sides during irradiation. For the 98 W cases, the larger beam diameter required a 53 % longer exposure time to achieve perforation, highlighting the role of power density in damage progression. Post-irradiation analysis using scanning electron microscopy (SEM), ultrasonic C-scans, and micro-focused X-ray computed tomography (micro-CT) revealed fibre sublimation, matrix decomposition, cone-shaped perforations, and interlaminar cracking. The results provide valuable insights into how CFRP materials respond to high-intensity laser exposure and can support the development of strategies to mitigate damage and improve structural performance in real-world applications.